Is there a safe no radiation option for endoscopic kidney stone treatment in children? multicenter results of modified retrograde intrarenal surgery without fluoroscopy in pediatric patients - Ozan, Tunc; Karakeci, Ahmet; Yilmaz, Kemal; Pirincci, Necip; Osmanlioglu, Fatih; Yuvanc, Ercan; Orhan, Irfan (Springer, 2025)
The practice of fluoroscopy during pediatric endoscopic kidney stone procedures requires attention because of radiation concerns that demand new treatment methods. This study aimed to present the multicentric results of single guide wire flexible ureterorenoscopy (URS) and retrograde intrarenal surgery (RIRS) procedures without fluoroscopy and an ureteral access sheath (UAS) in treating kidney stones in pediatric patients. Moreover, we aim to evaluate the efficacy and safety of this procedure to ascertain the feasibility of this radiation-free therapeutic intervention for treating kidney stones in children. A retrospective analysis was done on the data of 105 pediatric patients who underwent retrograde intrarenal surgery (RIRS) treatment in two tertiary healthcare centers without fluoroscopy and UAS between May 2014 and May 2024. Of these 105 patients evaluated, 74 (70.5%) were male and 31 (29.5%) were female. The patients had a mean age of 71 +/- 4 (ranging from 6 to 204) months. The mean size of stones was 9.3 +/- 5 (ranging from 6 to 20) mm, and the average operation time was 51 (ranging from 31 to 98) minutes. Additionally, in 24 (22.8%) patients, the flexible URS could not proceed through the ureteral orifice. Thus, a double J stent was inserted, and the surgical procedure was repeated one month later without any complications. However, 2 (1.9%) of the patients experienced postoperative fever, and 6 (5.7%) patients had minor complications related to haematuria. Stone-free status was observed in 87 out of 105 patients (82.9%). Despite using a single guide wire without fluoroscopy and UAS in treating kidney stones in pediatric patients, the RIRS procedure is technically effective and safe. It may be considered a viable non-surgical procedure that is effective in safeguarding pediatric patients from the harmful effects of radiation, rendering it a promising alternative for pediatric urolithiasis management.
Keywords: Pediatric urolithiasis; Retrograde intrarenal surgery; Fluoroscopy